2021
DOI: 10.1016/j.isci.2021.102422
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of the shortest extended synaptotagmin with only two C2 domains from Trypanosoma brucei

Abstract: Summary Extended synaptotagmins (E-Syts) localize at membrane contact sites between the endoplasmic reticulum (ER) and the plasma membrane to mediate inter-membrane lipid transfer and control plasma membrane lipid homeostasis. All known E-Syts contain an N-terminal transmembrane (TM) hairpin, a central synaptotagmin-like mitochondrial lipid-binding protein (SMP) domain, and three or five C2 domains at their C termini. Here we report an uncharacterized E-Syt from the protist parasite Tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Like to all mammalian cells, E-Syts from T. brucei has an N-terminal transmembrane hairpin and a central synaptotagmin-like mitochondrial lipid binding protein (SMP). However, TbE-Syt contains only two C2 domains, named C2A and C2B in contrast to at least three C2 domains in all other reported E-Syts present in higher eukaryotic cells ( SahekiDe Camilli, 2017 ; Stepinac et al., 2021 ). The depletion of TbE-Syt had no significant effect in bloodstream form T. brucei but have deleterious effect in procyclic forms.…”
Section: The Second-order Role Of Er In Trypanosomatidsmentioning
confidence: 92%
See 2 more Smart Citations
“…Like to all mammalian cells, E-Syts from T. brucei has an N-terminal transmembrane hairpin and a central synaptotagmin-like mitochondrial lipid binding protein (SMP). However, TbE-Syt contains only two C2 domains, named C2A and C2B in contrast to at least three C2 domains in all other reported E-Syts present in higher eukaryotic cells ( SahekiDe Camilli, 2017 ; Stepinac et al., 2021 ). The depletion of TbE-Syt had no significant effect in bloodstream form T. brucei but have deleterious effect in procyclic forms.…”
Section: The Second-order Role Of Er In Trypanosomatidsmentioning
confidence: 92%
“…The depletion of TbE-Syt had no significant effect in bloodstream form T. brucei but have deleterious effect in procyclic forms. Immunocytochemistry analysis showed that TbE-Sys co-localizes to both BiP, at the central ER close to nuclear envelope, and (FAZ1) a marker protein of unique flagellar attachment zone (FAZ) – associated cortical ER ( Stepinac et al., 2021 ). The FAZ is a large macromolecular structure located at the interface formed by the cellular and the flagellar membranes.…”
Section: The Second-order Role Of Er In Trypanosomatidsmentioning
confidence: 99%
See 1 more Smart Citation